Microglia-Centered Combinatorial Strategies Against Glioblastoma - Martins, Tomás A.; Schmassmann, Philip; Shekarian, Tala; Boulay, Jean-Louis; Ritz, Marie-Françoise; Zanganeh, Steven; vom Berg, Johannes; Hutter, Gregor (Frontiers in Immunology, 2020)
Tumor-associated microglia (MG) and macrophages (ΜΦ) are important components of the glioblastoma (GBM) immune tumor microenvironment (iTME). From the recent advances in understanding how MG and GBM cells evolve and interact during tumorigenesis, we emphasize the cooperation of MG with other immune cell types of the GBM-iTME, mainly ΜΦ and T cells. We provide a comprehensive overview of current immunotherapeutic clinical trials and approaches for the treatment of GBM, which in general, underestimate the counteracting contribution of immunosuppressive MG as a main factor for treatment failure. Furthermore, we summarize new developments and strategies in MG reprogramming/re-education in the GBM context, with a focus on ways to boost MG-mediated tumor cell phagocytosis and associated experimental models and methods. This ultimately converges in our proposal of novel combinatorial regimens that locally modulate MG as a central paradigm, and therefore may lead to additional, long-lasting, and effective tumoricidal responses.